The Code Mixing And Code Switching for Class XI Students SMA Negeri 6 Sarolangun Jambi - Ibnu Hapiz; Rahma Wati Hasyim; Djoko Susanto (IJER (Indonesian Journal of Educational Research), 2022)
The purpose of this study is to provide an overview of the form of code mixing, code switching models, aspects that trigger the creation of code mixing, and aspects that trigger code switching in dialogue within the scope of class XI students of SMA Negeri 6 Batang Asai. In reviewing the data, the researcher used a method in the form of a qualitative descriptive method. Observation, and documentation technique is the method used to collect data in this research, the method is by recording the dialogues that occur in the classroom during the learning activities and by interviewing the correspondents. The data analysis process is carried out in parallel with the data collection stage through various methods. Starting with data collection, data reduction, data presentation, and drawing conclusions. During the research the researchers obtained the results, namely: Forms, models, aspects that trigger the creation of code-mixing, and aspects that trigger code-switching.